Weekday-dependent long-term outcomes in gastrointestinal cancer surgery: a German population-based retrospective cohort study - Maier, Christopher; Schölch, Caroline; Zhu, Lei; Nzomo, Martial M.; L’hoest, Helmut; Marschall, Ursula; Reißfelder, Christoph; Schölch, Sebastian (International journal of surgery, 2023)
Background: - For most solid cancers, surgery represents the mainstay of curative treatment. Several studies investigating the effects of the weekday of surgery (WOS) on patient outcomes have yielded conflicting results. Barmer, the second-largest health insurance company in Germany, serves roughly 10% of the German population. The authors have used the Barmer database to evaluate how the weekday on which the surgery is performed influences long-term oncologic outcomes. - Methods: - For this retrospective cohort study, the Barmer database was used to investigate the effect of the WOS (Monday-Friday) on outcomes following oncological resections of the colorectum (n=49 003), liver (n=1302), stomach (n=5027), esophagus (n=1126), and pancreas (n=6097). In total, 62 555 cases from 2008 to 2018 were included in the analysis. The endpoints were overall survival (OS), postoperative complications, and the necessity for therapeutic interventions or reoperations. The authors further examined whether the annual caseload or certification as a cancer center influenced the weekday effect. - Results: - The authors observed a significantly impaired OS for patients receiving gastric or colorectal resections on a Monday. Colorectal surgery performed on Mondays was associated with more postoperative complications and a higher probability of reoperations. The annual caseload or a certification as a colorectal cancer center had no bearing on the observed weekday effect. There is evidence that hospitals schedule older patients with more comorbidities earlier in the week, possibly explaining these findings. - Conclusion: - This is the first study investigating the influence of the WOS on long-term survival in Germany. Our findings indicate that, in the German healthcare system, patients undergoing colorectal cancer surgery on Mondays have more postoperative complications and, therefore, require significantly more reoperations, ultimately lowering the OS. This surprising finding appears to reflect an attempt to schedule patients with higher postoperative risk earlier in the week as well as semi-elective patients admitted on weekends scheduled for surgery on the next Monday.
Online veröffentlicht: 5. Juli 2023
Gesehen am 21.08.2024